Involvement of baroreflex deficiency in the age-related loss of estrogen efficacy against cerebral ischemia - Wang, Lei; Wang, Jia; Shan, Qing; Shu, He; Guo, Jin-Min (Frontiers in Aging Neuroscience, 2023)
For post-menopausal women, stroke is complicated by the variable effects of estrogen therapy and the age-related therapeutic consequences involved. Estrogen therapy has been shown to have an age-dimorphic effect, which is neuroprotective in young females, but non-neuroprotective, even neurotoxic in acyclic females. We hypothesized that arterial baroreflex (ABR) and its downstream acetylcholine-α7 nicotinic acetylcholine receptor (α7nAChR) anti-inflammatory pathways are involved in estrogen efficacy toward cerebral ischemic damage. Our data showed that estrogen supplements contributed to ABR improvement and neuroprotection in adult, not aged, ovariectomized (OVX) rats. In adult rats, OVX-induced estrogen deficiency aggravated middle cerebral artery occlusion (MCAO), which induced brain infarction and reduced ABR function, with decreased α7nAChR expression of the brain and exaggerated inflammation following MCAO; these effects were significantly prevented by supplementation with estrogen. ABR impairment by sinoaortic denervation partly attenuated the estrogen effect on baroreflex sensitivity (BRS) and ischemic damage in adult rats, as well as α7nAChR expression and inflammatory response. These data suggested that ABR and acetylcholine-α7nAChR anti-inflammatory pathways are involved in the neuroprotection of estrogen in adult OVX rats. In contrast, aged rats exhibited more severe ischemic damage and inflammatory response than adult rats, as well as poorer baroreflex function and lower α7nAChR expression. Estrogen supplements did not improve BRS or confer neuroprotection in aged rats without affecting brain α7nAChR and post-ischemic inflammation. Most importantly, ketanserin restored ABR function and significantly postponed the onset of stroke in aged female strokeprone spontaneously hypertensive rats, whereas estrogen treatment failed to delay the development of stroke. Our findings reveal that estrogen is protective against ischemic stroke (IS) in adult female rats and that ABR played a role in this beneficial action. Dysfunction of ABR and unresponsiveness to estrogen in aged female rats may contribute to a reduced estrogen efficacy against cerebral ischemia.